CDK/CCN and CDKI Alterations for Cancer Prognosis and Therapeutic Predictivity. (29th January 2014) - Bonelli, Patrizia; Tuccillo, Franca Maria; Borrelli, Antonella; Schiattarella, Antonietta; Buonaguro, Franco Maria
Abstract : The regulation of cell growth and division occurs in an accurate sequential manner. It is dictated by the accumulation of cyclins (CCNs) and cyclin-dependent kinases (CDKs) complexes and degradation of CCNs. In human tumors, instead, the cell cycle is deregulated, causing absence of differentiation and aberrant cell growth. Oncogenic alterations of CCNs, CDKs, and CDKIs have been reported in more than 90% of human cancers, and the most frequent are those related to the G1 phase. Several molecular mechanisms, including gene overexpression, chromosomal translocations, point mutations, insertions and deletions, missense and frame shift mutation, splicing, or methylation, may be responsible for these alterations. The cell cycle regulators are involved in tumor progression given their association with cancers characterized by higher incidence of relapses and chemotherapy resistance. In the last decade anticancer drug researches focused on new compounds, able to target molecules related to changes in genes associated with tumor status. Recently, the studies have focused on the restoration of cell cycle control modulating molecular targets involved in cancer-cell alterations. This paper aims to correlate alterations of cell cycle regulators with human cancers and therapeutic responsivity.